2019
DOI: 10.3390/ijms21010052
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles and Epigenetic Modifications Are Hallmarks of Melanoma Progression

Abstract: Cutaneous melanoma shows a high metastatic potential based on its ability to overcome the immune system’s control. The mechanisms activated for these functions vary extremely and are also represented by the production of a number of extracellular vesicles including exosomes. Other vesicles showing a potential role in the melanoma progression include oncosomes and melanosomes and the majority of them mediate tumor processes including angiogenesis, immune regulation, and modifications of the micro-environment. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 114 publications
1
37
0
Order By: Relevance
“…The L-EVs, larger vesicles than 200 nm, include microvesicles/ectosomes, apoptotic bodies and large oncosomes, while S-EVs include exosomes and exomeres. Microvesicles (0.2-0.5 µm) are large extracellular vesicles originated from the plasma membrane by direct shedding in response to cellular activation or stress, apparently in a manner similar to that of retroviruses [20][21][22][23][24]. Baig et al [25] also found that microvesicles originate at special lipid raft domains of the plasma membrane.…”
Section: General Aspects Of Evsmentioning
confidence: 99%
See 2 more Smart Citations
“…The L-EVs, larger vesicles than 200 nm, include microvesicles/ectosomes, apoptotic bodies and large oncosomes, while S-EVs include exosomes and exomeres. Microvesicles (0.2-0.5 µm) are large extracellular vesicles originated from the plasma membrane by direct shedding in response to cellular activation or stress, apparently in a manner similar to that of retroviruses [20][21][22][23][24]. Baig et al [25] also found that microvesicles originate at special lipid raft domains of the plasma membrane.…”
Section: General Aspects Of Evsmentioning
confidence: 99%
“…Baig et al [25] also found that microvesicles originate at special lipid raft domains of the plasma membrane. When cells undergo apoptosis, they dissociate into membrane-bound apoptotic bodies (0.8-5 µm), which might contain genomic DNA [20,26]. In addition, in cancer cells, the larger EVs (1-10 µm), termed large oncosomes, can bleb off the cell membrane [20,27].…”
Section: General Aspects Of Evsmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if not encoding protein products, noncoding RNA (ncRNAs) are critical regulators of cellular processes. In particular, miRNAs are small (approximately 22 base pairs) ncRNAs that act as epigenetic modulators by targeting the turnover of specific mRNAs, through which they regulate a huge number of processes, including signal transduction, cell cycle, cell proliferation and metabolism, all of them playing key roles in cancer [68] , [69] . miRNAs have been investigated for their capability to participate in the bone homing process and act as potential biomarkers of BC skeletal colonization ( Table 2 ).…”
Section: Application Of “Omics” Sciences To the Early Identification mentioning
confidence: 99%
“…Those bearing a nano-sized diameter (30-100 nm) are currently referred to as small-EVs or Exo (63,64). They are involved in intercellular communication by delivering cargos of active molecules including proteins, messenger RNAs, non-coding RNAs, and DNA fragments from one to another cell (65). Many studies in CRC revealed that Exo are involved in tumor progression and metastasis, as well as in tumor resistance against either cytotoxic or targeting agents (66,67).…”
Section: Exosomesmentioning
confidence: 99%